THE ROLE OF “VR”, “AR”, “MR”, AND “3D” TECHNOLOGIES IN PREPARING CHEMISTRY TEACHERS FOR INTERNATIONAL TALIS STUDIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the role of VR (Virtual Reality), AR (Augmented Reality), MR (Mixed Reality), and 3D technologies in preparing chemistry teachers for participation in international TALIS (Teaching and Learning International Survey) studies. The research highlights the importance of integrating immersive and interactive digital technologies into chemistry teacher professional development to enhance pedagogical competence, digital literacy, and innovative teaching practices. Particular attention is paid to the potential of VR, AR, MR, and 3D technologies to support visualization of abstract chemical concepts, virtual laboratory experiments, and simulation-based learning environments. The article argues that the systematic use of these technologies contributes to the development of teachers’ reflective practice, classroom management skills, and readiness for international assessment frameworks such as TALIS. The findings emphasize that technology-enhanced training not only improves the quality of chemistry education but also aligns national teacher preparation systems with global educational standards and trends.